INCUBATION TEMPERATURE FOR TOTAL BACTERIAL COUNT OF FROZEN SEA FOOD - VARMA, P R. G; MATHEN, CYRIAC; MATHEW, ANNAMMA; THOMAS, FRANCIS; IYER, H KRISHNA (Fishery Technology, 2017)
Effect of incubation temperatures of 37Â°C ambient and 5-10Â°C on total plate count of commercial frozen prawns, squids, cuttle fish and froglegs were studied. Results indicate that incubation at ambient temperature gives the best results.